GGE-Biplot Analysis for Soybean Varieties Suitability in an Agroforestry System based on Kayu Putih Stands - Taufan Alam; Priyono Suryanto; Aprilia Ike Nurmalasari; Budiastuti Kurniasih (Caraka Tani: Journal of Sustainable Agriculture, 2019)
The existence of genotype and environment (G x E) interaction causes difficulty in selecting suitable varieties of soybean in an agroforestry system based on kayu putih stands. This study aimed to determine the suitability of adaptive, stable and high yield soybean varieties in an agroforestry system based on kayu putih stands by using GGE-Biplot analysis. The experiment was conducted from May to August 2018 at Menggoran Forest Resort, Playen District, Gunung Kidul Regency, Special Region of Yogyakarta, Indonesia. The experiment was conducted using a randomized complete block design (RCBD) with five block as replications. The first factor was soil type in Menggoran Forest Resort, consisting of Lithic Haplusterts, Vertic Haplustalfs and Ustic Endoaquerts. The second factor was soybean varieties, consisting of Anjasmoro, Argomulyo, Burangrang, Dering I, Devon I, Gema and Grobogan. The observation was carried out on seed dry weight of soybean per hectare. The data were analyzed using Combined Analysis of Variance (ANOVA) with α = 5% and GGE-Biplot. Dering I was the most suitable varieties in an agroforestry system based on kayu putih stands and showed the mean of highest yield of 1.22 tons ha-1.